2018
DOI: 10.1038/s41426-018-0162-6
|View full text |Cite
|
Sign up to set email alerts
|

Rv2346c enhances mycobacterial survival within macrophages by inhibiting TNF-α and IL-6 production via the p38/miRNA/NF-κB pathway

Abstract: The intracellular survival of Mycobacterium tuberculosis (Mtb) has a central role in the pathogenesis of tuberculosis. Mtb Rv2346c is a member of 6-kDa early secreted antigenic target family of proteins, which are known to inhibit the host immune responses to promote bacillary persistence in macrophages. However, the mechanism through which Rv2346c participates in Mtb pathogenesis is unclear. In the present study, recombinant Rv2346c protein was synthesized and used to treat Bacillus Calmette–Guérin (BCG)-infe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
24
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 34 publications
(25 citation statements)
references
References 41 publications
1
24
0
Order By: Relevance
“…3F) (85). In this same showed an increase in miR-155 levels (102), as well as the human monocytic leukemia cell line (U937 cells) infected with BCG, where the upregulation was further enhanced by stimulating with Rv2346c, a putative ESAT-6-like protein of M. tuberculosis (103).…”
Section: Role Of Validated Mirna In Different Stages Of Diseasementioning
confidence: 64%
“…3F) (85). In this same showed an increase in miR-155 levels (102), as well as the human monocytic leukemia cell line (U937 cells) infected with BCG, where the upregulation was further enhanced by stimulating with Rv2346c, a putative ESAT-6-like protein of M. tuberculosis (103).…”
Section: Role Of Validated Mirna In Different Stages Of Diseasementioning
confidence: 64%
“…We also included the recently discovered in vivo -expressed antigens (Rv2346/47c, Rv2431c, Rv3614/15c, Rv3865) that have not been studied extensively in humans, but are believed to be important virulence factors ( Commandeur et al., 2013 ). Rv2346 and Rv2347c are ESAT-6 like proteins and associated with downregulation of IL-6 and TNF-α enabling survival of bacteria inside macrophages ( Malen et al., 2007 ; Yao et al., 2018 ). Rv2431c is a prolin-glutamic acid family protein, and its function is yet to be understood ( Malen et al., 2007 ).…”
Section: Discussionmentioning
confidence: 99%
“…The experiment proved that in A20-deficient macrophages, the production of proinflammatory factors (TNF-α, IL-1β) was increased and M. tuberculosis survival was attenuated ( 22 ). In infected macrophages, experiments confirmed that Rv2346c, an ESAT-6-like protein, which augmented the phosphorylation of P38, simultaneously upregulates miR-155 and miR-99b, which reduced the production of TNF-α and IL-6 by inhibiting the activation of NF-κB, thereby facilitates intracellular M. tuberculosis survival ( 23 ).…”
Section: Host Cell Microrna Involved In M Tuberculosis Infectionmentioning
confidence: 97%